Assessing extreme loads on a tidal turbine using focused wave groups in energetic currents. (May 2019) - Draycott, S.; Nambiar, A.; Sellar, B.; Davey, T.; Venugopal, V.
Abstract: Tidal stream turbines are subject to large hydrodynamic loads, including those induced by extreme waves. Scale model testing in the laboratory plays an important role in ensuring that full scale tidal turbines are designed and operated in a manner that is appropriate for harsh ocean environments where waves and tidal currents coexist. For the first time, a fully-instrumented scaled tidal turbine is tested in short-duration focused wave groups representative of extreme environmental load cases expected at energetic tidal sites. In this paper, the subsequent variations in rotor-based loads, power and blade root bending moments are reported. These measurements are found to strongly follow the spectral and temporal form of the focused wave conditions, and peak loads and power output are found to exceed current-only values by 85% and 200% respectively. These rotor-averaged values display a high level of repeatability, demonstrating the suitability of focused waves for testing seabed-mounted tidal turbines. Extreme blade loads, which are dependent on angular position relative to wave phase, are captured through rapidly obtained repeat tests. New insight is subsequently gained into loading and response of tidal turbines in extreme sea conditions. Highlights: Focused wave groups successfully produced in energetic currents of 0.8 m/s. Fully-instrumented tidal turbine tested in these extreme wave-current conditions. Peak loads and power output exceed current-only values by 80% and 200% respectively. Measured loads follow temporal and spectral form of generated focused waves.